Pregnancy (im)possibilities: identifying factors that influence sexual minority women's pregnancy desires. (15th March 2020) - Carpenter, Emma; Everett, Bethany G.; Greene, Madelyne Z.; Haider, Sadia; Hendrick, C. Emily; Higgins, Jenny A.
ABSTRACT: Sexual minority women (SMW) face both increased risk for unintended pregnancy and barriers to achieving wanted pregnancy, but little research investigates SMW's pregnancy desires. To fill this gap, we conducted five focus groups and 11 in-depth interviews with 20-30-year-old SMW in three US cities. Findings highlight that the heteronormative pregnancy planning paradigm lacks salience for SMW. While some SMW clearly wish to avoid pregnancy, many others are unsure, and factors influencing this uncertainty include relationship context, anticipating logistical barriers, and discord between queer identity and pregnancy.